Pemberian Fasilitas Penananaman Modal Asing Sebagai Upaya Peningkatan Investasi Dikaitkan Dengan Pemberlakuan Kesepakatan Masyarakat Ekonomi Asean - Orinton purba (Universitas Jayabaya, 2016)
ASEAN countries have agreed to establish the ASEAN Community in 2015 through the ASEAN Charter, signed on 20 November 2007 in Singapore. This agreement is based on three (3) pillars, namely the ASEAN Political Community (APC), ASEAN Economic Community (AEC) and ASEAN SocioCultural Community (ASCC). In increasing investment in a country, one of the commonly used method is to provide fiscal and non fiscal facilities for investors.The research method used is the legal normative research which is done carried out to obtain the necessary data related to the research hypothesis. The data used is secondary data, which consists of primary legal materials and secondary legal materials and tertiary legal materials. For data analysis was conducted using qualitative analysis.